Brain proteomic changes by histone deacetylase inhibition after traumatic brain injury. Issue 1 (24th March 2021) - Pumiglia, Luke; Williams, Aaron M; Kemp, Michael T; Wakam, Glenn K; Alam, Hasan B; Biesterveld, Ben E
Abstract : Background: Traumatic brain injury (TBI) is a leading cause of morbidity and mortality. There are currently no cytoprotective treatments for TBI. There is growing evidence that the histone deacetylase inhibitor valproic acid (VPA) may be beneficial in the treatment of TBI associated with hemorrhagic shock and in isolation. We sought to further evaluate the mechanistic underpinnings of this demonstrated efficacy via proteomic analysis of injured brain tissue. Methods: Swine were subjected to TBI via controlled cortical impact, randomized to treatment with VPA or control and observed for 6 hours. The brains of the pigs were then sectioned, and tissue was prepared and analyzed for proteomic data, including gene ontology (GO), gene-set enrichment analysis and enrichment mapping, and network mapping. Results: Proteomic analysis demonstrated differential expression of hundreds of proteins in injured brain tissue after treatment with VPA. GO analysis and network analyses revealed groups of proteins and processes that are known to modulate injury response after TBI and impact cell fate. Processes affected included protein targeting and transport, cation and G-protein signaling, metabolic response, neurotransmitter response and immune function. Discussion: This proteomic analysis provides initial mechanistic insight into the observed rescue of injured brain tissue after VPA administration in isolated TBI. Level of evidence: Not applicable (animal study).